A comparative study on echocardiographic evaluation of left ventricular mass and function in normotensive diabetic and non-diabetic patient - Mukhopadhyay, Tanmay; Sarkar, Pankaj; Naskar, Somnath; Biswas, Uttam; Islam, SK Saidul (Asian Journal of Medical Sciences, 2021)
Background: Cardiovascular complications account for the highest mortality in diabetic patients, mainly due to coronary artery disease and congestive heart failure. Left ventricular hypertrophy (LVH) is an ominous prognostic sign and an independent risk factor for cardiac events which is frequently present in patients living with diabetes. Aims and Objectives: The aim of the study was to evaluate the LV mass and function in normotensive diabetes patients without antihypertensive medication. Materials and Methods: 100 normotensive diabetic patients were in study group and 100 control patients were studied. Hypertension and other known causes of LVH were excluded from the study. Data were analyzed using proper statistical method. Results: Left ventricular mass index (LVMI) is significantly higher in diabetic patients as compared to control population (P<0.001). It was also observed that the means of the left ventricular posterior wall thickness, interventricular septal thickness, and the left ventricular internal diameter during diastole (in all cases P<0.001) were statistically significantly high in diabetic patients in comparison to healthy control subjects. We have found that a significant systolic dysfunction in diabetic group and diastolic dysfunction also very common in diabetic group than the control group. The LVMI also increased in patients who have longer duration of diabetes and poor glycemic control. Conclusion: LVM is significantly higher in patients of type 2 diabetic without having hypertension, albuminuria, and apparent ischemic heart disease as compared to healthy controls. LVM in diabetic patients increases with duration of diabetes and is positively correlated with HbA1c and blood sugar level.